Study of Age of Seedlings at Transplanting on Growth Dynamics and Yield of Rice under Alternating Flooding and Suspension of Irrigation of Water Management - Ranamukhaarachchi, G.A. Sanjeewanie Ginigaddara; S.L. (Recent Research in Science and Technology, 2011)
Age of seedlings at transplanting is considered for influencing grain yield in water scarce rice production systems, primarily by laying the foundation for determining the number of panicles at harvest. This experiment investigated plant growth, yield and yield components of rice when transplanted at varying ages under alternating flooding and suspending irrigation in water management for saving water.Ã‚Â In a greenhouse study, nine ages of seedlings starting from 4 to 12 days were transplanted in pots and the performance of each age was compared with a direct-seeded crop in a completely randomized design with five replicates. Soil moisture content (SMC) in the 0-15, 15-25 and 25-50 cm soil layers were monitored. SMC reached near the lowest level of readily available water (RAW), but never reached below RAW during the first suspension of irrigation in all the treatments. However, SMC reached PWP in the 15-25 cm soil layer at the second period of suspension of irrigation. The number of tillers, leaf area per hill, plant height and above ground non-grain biomass did not differ between direct-seeded rice (DSR) and transplanted rice (TPR) with 4-12-day old seedlings. Maximum tillering occurred between 5 and 6 weeks after establishment in all age groups of seedlings. However, root depth, total root length, root dry weight and shoot to root ratio were significantly greater in DSR than TPR.Ã‚Â Age of seedlings at transplanting had a significant effect on number of productive tillers per hill, filled grains per panicle, panicle length, 1000-grain weight, grain yield and panicle setting rate. However, harvest index was not significantly affected. Establishment of rice by direct seeding and transplanting up to 12 days did not differ in handling the transplanting shock and resuming normal growth phase rapidly. And also, there was no difference in the tillering potential and the growth dynamics of seedlings of all ages used, but 9-day old seedlings had higher yield under alternating flooding and suspending irrigation compared to other ages of seedling and water management.